Design, Synthesis, and In Vitro and In Silico Biological Exploration of Novel Pyridine-Embedded 1,3,4-Oxadiazole Hybrids as Potential Antimicrobial Agents - Shivakumara K. N.; Basavarajaiah S. M.; Nagesh G. Y.; Prashantha K.; Yogesh M.; Abhishek N. R.; Odesha H. N. (Journal of Chemistry)
Antibiotic resistance represents a significant public health challenge in the current century. The β-lactam antibiotics, together with carbapenems, are inactivated by zinc-dependent bacterial enzymes called metallo-β-lactamases (MBLs). Presently there are no clinically permitted MBL inhibitors, and to produce such drugs, it is indispensable to comprehend their inhibitory action. We investigated an efficient synthesis of pyridine-embedded 1,3,4-oxadiazole hybrids (3a-c) and their antimicrobial activity against different microbial strains. The compounds were characterized by spectral techniques (viz., IR, NMR, and mass). The in vitro antibacterial and antifungal activity was also performed; the compounds (3a-c) displayed excellent antimicrobial activity. The in silico docking studies were evaluated with proteins New Delhi Metallo-Beta-lactamase-1 (NDM-1) and Mycobacterium tuberculosis enoyl reductase (INHA). All the compounds demonstrated a significant binding affinity for the docked proteins. Additionally, molecular dynamics were disclosed for compounds (4a-c).